2005
DOI: 10.1002/asi.20180
|View full text |Cite
|
Sign up to set email alerts
|

The effects of expertise and feedback on search term selection and subsequent learning

Abstract: Query formation and expansion is an integral part of nearly every effort to search for information. In the work reported here we investigate the effects of domain knowledge and feedback on search term selection and reformation. We explore differences between experts and novices as they generate search terms over 10 successive trials and under two feedback conditions. Search attempts were coded on quantitative dimensions such as the number of unique terms and average time per trial, and as a whole in an attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 30 publications
1
75
1
Order By: Relevance
“…29 It was also found that with an increase in the level of domain knowledge, users tend to use more terms in queries; domain experts use more effective strategy, conduct more complex searches, and incorporate more unique terms. 30 Many studies considered how representatives of a specific domain or discipline search for information. Studies have shown that scientists' searching is usually aimed at specific questions or problems that they face when conducting an experiment, writing up results, or checking the accuracy of information in hand.…”
Section: Domain Knowledge and User Searchingmentioning
confidence: 99%
“…29 It was also found that with an increase in the level of domain knowledge, users tend to use more terms in queries; domain experts use more effective strategy, conduct more complex searches, and incorporate more unique terms. 30 Many studies considered how representatives of a specific domain or discipline search for information. Studies have shown that scientists' searching is usually aimed at specific questions or problems that they face when conducting an experiment, writing up results, or checking the accuracy of information in hand.…”
Section: Domain Knowledge and User Searchingmentioning
confidence: 99%
“…For health consumers, a fundamental poverty in the mental representation of the medical domain underlies issues with terminology, and it is likely to affect three stages of information retrieval outlined by Keselman and her colleagues [43]: (i) the formation of a theory or hypothesis based on background knowledge, (ii) generation of a search goal, and (iii) evaluation of search results. Domain knowledge influences search strategies and the ability to benefit from help tools [44][45][46][47]. Therefore, the success of efforts aimed at CHV is likely to be limited without mechanisms for helping the consumer form a richer mental representation of the medical or health issue for which they seek information.…”
Section: Obstacles For Chv and Nlpmentioning
confidence: 99%
“…However, a lot more can be done. For example, word choices might reveal the age of the user [31] or their level of domain expertise [15], which in turn would have implications for the medical meaning of symptoms. We also have not yet considered formulation nuances of queries other than the landmark query, which might hold much richer information.…”
Section: Discussionmentioning
confidence: 99%